Effect of annealing on the thermal and functional properties of jicama (Pachyrhizus erosus) starch - Ventinilla, Kyla Mariz R.
Annealing is a physical starch modification method recognized for enhancing the thermal and functional properties of native starch for broader industrial applications. In this study, jicama (Pachyrhizus erosus) starch was extracted and subjected to annealing treatment at different temperatures (T = 45°C, 50 °C, and 55°C) in a 1:6 starch/water ratio for 22 h. The starch has an extraction yield of 1.48% (wet basis). The thermal properties, functional properties, and water activity of the untreated and annealed starches were investigated. The annealing treatment resulted in increased water absorption (2.17 to 2.40 g/g), least gelation concentration (16% to 20%), and water activity (0.54 to 0.92). Conversely, it led to decreased solubility (6.76% to 4.31%), swelling power (10.39 to 7.66 g/g), oil absorption (2.05 to 1.55 g/g), and bulk density (0.64 to 0.48 g/mL). The onset temperature (51.67-56.33°C), peak temperature (62.66-76.54°C), conclusion (80.75-85.32°C) temperature, and enthalpy of gelatinization (109.11-124.01 J/g) increased, indicating improved thermal stability compared to the native starch. These modifications suggest that annealed jicama starch may be well-suited for use in products such as noodles, biodegradable packaging films, and other processed food items.